Pressure relieving support surfaces (PRESSURE) trial: cost effectiveness analysis. Issue 7555 (1st June 2006) - Iglesias, Cynthia; Nixon, Jane; Cranny, Gillian; Nelson, E Andrea; Hawkins, Kim; Phillips, Angela; Torgerson, David; Mason, Su; Cullum, Nicky
Abstract: Objective To assess the cost effectiveness of alternating pressure mattresses compared with alternating pressure overlays for the prevention of pressure ulcers in patients admitted to hospital. Design Cost effectiveness analysis carried out alongside the pressure relieving support surfaces (PRESSURE) trial; a multicentre UK based pragmatic randomised controlled trial. Setting 11 hospitals in six UK NHS trusts. Participants Intention to treat population comprising 1971 participants. Main outcome measures Kaplan Meier estimates of restricted mean time to development of pressure ulcers and total costs for treatment in hospital. Results Alternating pressure mattresses were associated with lower overall costs (£283.6 per patient on average, 95% confidence interval - £377.59 to £976.79) mainly due to reduced length of stay in hospital, and greater benefits (a delay in time to ulceration of 10.64 days on average, - 24.40 to 3.09). The differences in health benefits and total costs for hospital stay between alternating pressure mattresses and alternating pressure overlays were not statistically significant; however, a cost effectiveness acceptability curve indicated that on average alternating pressure mattresses compared with alternating pressure overlays were associated with an 80% probability of being cost saving. Conclusion Alternating pressure mattresses for the prevention of pressure ulcers are more likely to be cost effective and are more acceptable to patients than alternating pressure overlays.